2011
DOI: 10.1371/journal.pone.0022147
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Dendritic Cells Reveals Important Mechanisms Associated with Predisposition to Staphylococcus Infections

Abstract: Background Staphylococcus aureus is a major pathogen of humans and animals and emerging antibiotic-resistant strains have further increased the concern of this health issue. Host genetics influence susceptibility to S. aureus infections, and the genes determining the outcome of infections should be identified to find alternative therapies to treatment with antibiotics. Here, we used outbred animals from a divergent selection based on susceptibility towards Staphylococcus infection to explore host immunogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 64 publications
(57 reference statements)
1
13
0
3
Order By: Relevance
“…These authors have suggested that, in selection of ewes for resistance to mastitis, use of reduced log-transformed somatic cell score may be employed as an indirect trait. Recently, Bonnefont et al (2011) andToufeer et al (2011) have used a 15 K ovine-specific microarray for transcriptional profiling to study the biological pathways and genes determining the underlying susceptibility and resistance against staphylococcal mammary infections, which would help identification of biological pathways and genes in mastitis resistance.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…These authors have suggested that, in selection of ewes for resistance to mastitis, use of reduced log-transformed somatic cell score may be employed as an indirect trait. Recently, Bonnefont et al (2011) andToufeer et al (2011) have used a 15 K ovine-specific microarray for transcriptional profiling to study the biological pathways and genes determining the underlying susceptibility and resistance against staphylococcal mammary infections, which would help identification of biological pathways and genes in mastitis resistance.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Methods were essentially as described before (54). Briefly, cDNA from all samples was preamplified using a pool of forward and reverse primers.…”
Section: Reverse Transcriptionmentioning
confidence: 99%
“…Our previous experiments are not in favor of these hypotheses. Indeed, the gene expression profiles of Staphylococcus spp-mastitis-resistant and -susceptible animals have already been studied in two other cell types: MSC collected after S. epidermidis or S. aureus inoculations of the mammary gland (8) and S. aureus-stimulated DC (54) with two groups of four (54) or six (8) sheep. In both cases significant differences were detected.…”
Section: Differences Between Staphylococcus Spp-mastitis Resistant Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the gene expression profiling has been applied to exploration of host-pathogen interactions [12,13]. The identification of gene expression signatures indicative of virus subtypes using microarray technology has increased provided novel insights into the molecular basis of viral infection [12].…”
Section: Introductionmentioning
confidence: 99%